Efeitos de alterações de vazão em comunidades bentônicas e interações tróficas com a ictiofauna bentófaga - Taynan Henriques Tupinambás (2013)
In the unlike way of the socio-economic benefits provided by the reservoirs (e.g. power generation, human supply, flood regulation and activities of leisure and tourism) the reservoir construction also causes environmental impacts. The river damming influences the natural hydrological regime, which changes the frequency, duration and magnitude of natural flow regimes. These changes alter important physical and chemical characteristics of water and sediment and consequently the hábitats available for shelter, feeding and reproduction of biological communities, which influence the aquatic ecosystems functioning. Among the biological communities used as tools in aquatic impact assessments, the benthic macroinvertebrates have been highlighted. These organisms play a central role in riverine food webs by converting algae and organic detritus in animal tissue, available for feeding fish. Trough the evaluation of composition, structure and function of these communities, it has been possible to detect and quantify their responses to impacts caused by flow changes downstream of reservoirs. The present thesis evaluated the influence of inter and intraseasonal and daily flow changes downstream Itutinga reservoir, and assess the efficiency of fish stomach analysis as a tool in environmental assessments. Flow manipulation experiments were performed downstream of Itutinga Reservoir, Minas Gerais, over two years (2010 and 2011) under different flow values in different hábitats types (backwater, beach and rapids). In the first chapter the responses of benthic macroinvertebrate communities to daily flow peaking were evaluated, simulating the daily hours of power generation peaking. Weobserved that benthic macroinvertebrate communities are altered by daily flow peakings only in the dry period. These alterations were influenced by changes in basic physical and chemical water characteristics, related to the expansion flow onto the adjacent floodplain, resulting in increased input of allochthonous organic material and sediments, such as turbidity, total dissolved solids and nutrients. In the second chapter, the responses of benthic macroinvertebrate communities to inter-seasonal and intra-seasonal flow alterations were evaluated. The intra-seasonal variations (high and low values) influenced the abundance, composition and structure of biological communities. The communities were structured based in the sediment heterogeneity and composition, forming the available micro-hábitats. In the third chapter the effectiveness of the analysis of stomach contents of benthophagous fish species as a tool to assess macroinvertebrate communities were evaluated. Positivecorrelations have been detected between the benthic macroinvertebrate taxa from fish stomachs to those taxa from sediment. The taxa accumulation curves show that Eigenmannia virescens (Sternopygidae - Gymnotiformes) had a rapid ascending curve than the sediment samples. In addition, fish stomach samples had higher dispersion values than sediment samples, which revealed their potential in assessments of benthic communities. The fourth chapter aimed to disseminate scientific data obtained from Chapters 1 and 2. It is presented in a dynamic text, with didactic and illustrative graphics, tables and figures that may contribute to the dissemination of knowledge on dams impacts to the aquatic ecosystems functioning. It was concluded that benthic macroinvertebrate communities are sensitive to changes in flow, either in temporal or spatial scales. Other conclusion was that the prediction, evaluation and monitoring of the dam impacts, especially in the downstream stretches, should be considered during the planning, construction and operation of reservoirs in Brazil. Thus, as showed, themacroinvertebrate communities provide relevant information on the functioning of aquatic ecosystems, and can be used as a tool in Environmental Flows requirements.